2017
DOI: 10.1089/hum.2016.111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dose and Safety of AAV7m8 and AAV8BP2 in the Non-Human Primate Retina

Abstract: Within the next decade, we will see many gene therapy clinical trials for eye diseases, which may lead to treatments for thousands of visually impaired people around the world. To target retinal diseases that affect specific cell types, several recombinant adeno-associated virus (AAV) serotypes have been generated and used successfully in preclinical mouse studies. Because there are numerous anatomic and physiologic differences between the eyes of mice and "men" and because surgical delivery approaches and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 31 publications
3
107
0
Order By: Relevance
“…We and others have shown transduction of macaque cones using AAV variants with ubiquitous promoters (16,(29)(30)(31)(32), but achieving cone transduction by vitreally administered AAV has only been possible at high doses, leading to inflammation (16,29). We reasoned that foveal cone targeting could be achieved if we use a strong cone-specific promoter at lower intravitreally injected AAV doses compatible with safety (29,33). To test if such "dose sparing" is possible, we injected 2 macaque eyes with AAV2-7m8-PR1.7-GFP and 2 other macaque eyes were injected with AAV2-7m8-GFP under the control of the cytomegalovirus (CMV) promoter at a dose of 1 × 10 11 viral genomes (vg) per eye (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown transduction of macaque cones using AAV variants with ubiquitous promoters (16,(29)(30)(31)(32), but achieving cone transduction by vitreally administered AAV has only been possible at high doses, leading to inflammation (16,29). We reasoned that foveal cone targeting could be achieved if we use a strong cone-specific promoter at lower intravitreally injected AAV doses compatible with safety (29,33). To test if such "dose sparing" is possible, we injected 2 macaque eyes with AAV2-7m8-PR1.7-GFP and 2 other macaque eyes were injected with AAV2-7m8-GFP under the control of the cytomegalovirus (CMV) promoter at a dose of 1 × 10 11 viral genomes (vg) per eye (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, our data in NHPs show for the first time to our knowledge noninvasive, specific, and high-level primate foveal cone transduction compatible with optogenetic applications for vision restoration. However, as promoter activity shows important variations across species (16,29,36), we deemed it necessary to validate PR1.7 in human cells and tissues. Due to the lack of a good human photoreceptor cell line or other model that could be used to test efficiency of cone promoter activity, we used 3-D retinal organoids derived from human induced pluripotent stem cells (iPSCs) (37).…”
Section: Resultsmentioning
confidence: 99%
“…Several AAVs have been tested for retinal gene delivery via the intravitreal route, and some have evoked safety concerns that have not been fully addressed at this stage. 25,43 For example, a recent study suggested that the engineered AAV variant AAV2-7m8 might be more immunogenic when used at high doses via intravitreal injections. 25 Therefore, we chose AAV2 for its known safety and efficacy in targeting RGCs in NHP studies [27][28][29] and the large body of work using this vector in human clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…25,43 For example, a recent study suggested that the engineered AAV variant AAV2-7m8 might be more immunogenic when used at high doses via intravitreal injections. 25 Therefore, we chose AAV2 for its known safety and efficacy in targeting RGCs in NHP studies [27][28][29] and the large body of work using this vector in human clinical trials. [20][21][22][23]44 High-level expression with a limited viral dose being a major parameter in obtaining functional expression, we designed a new RGC-specific promoter, driving strong transgene expression in RGCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation